Tactical Design as a Strategy for Innovation - Alessandro Spennato; Paolo Di Nardo (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Tactical design has emerged as an innovative strategy for transforming public spaces through temporary, flexible and participatory interventions. This study analyses its potential for urban innovation, focusing on methodologies, impacts and challenges. Through a mixed approach that includes field observations, interviews and case study analyses, the research highlights how tactical design favours social inclusion and the activation of collaborative networks. The project results at the University of Perugia demonstrate that small-scale interventions can improve the perception of urban spaces, strengthening the sense of belonging and the quality of the experience. The involvement of students emphasised the educational and transformative value of tactical design. The study contributes to the debate on experimental urban planning, highlighting the need to integrate these approaches into sustainable urban strategies supported by institutions.